Hemophagocytosis in Experimental Visceral Leishmaniasis by Leishmania donovani - Morimoto, Ayako (PLoS Negl Trop Dis, 2016)
Hemophagocytosis is a phenomenon in which macrophages phagocytose blood cells. There are reports on up-regulated hemophagocytosis in patients with infectious diseases including typhoid fever, tuberculosis, influenza and visceral leishmaniasis (VL). However, mechanisms of infection-associated hemophagocytosis remained elusive due to a lack of appropriate animal models. Here, we have established a mouse model of VL with hemophagocytosis. At 24 weeks after infection with 1 x 10(7) Leishmania donovani promastigotes, BALB/cA mice exhibited splenomegaly with an average tissue weight per body weight of 2.96%. In the tissues, 28.6% of macrophages contained phagocytosed erythrocytes. All of the hemophagocytosing macrophages were parasitized by L. donovani, and higher levels of hemophagocytosis was observed in heavily infected cells. Furthermore, more than half of these hemophagocytes had two or more macrophage-derived nuclei, whereas only 15.0% of splenic macrophages were bi- or multi-nuclear. These results suggest that direct infection by L. donovani causes hyper-activation of host macrophages to engulf blood cells. To our knowledge, this is the first report on hemophagocytosis in experimental Leishmania infections and may be useful for further understanding of the pathogenesis.